Effects of Thermal Processing Methods on the Quality Changes of Thick-Shelled Mussels - WANG Shaoping, LI Kaihui, TU Chuanhai, WANG Jiaxing, FANG Chuandong, ZHANG Bin (Shipin Kexue)
To explore the quality changes of mussels during thermal processing, the effects of five thermal processing methods: boiling water heating (BH), steam heating (SH), microwave heating (MH), vacuum water bath heating (VH), and air circulation heating (AH) on the drip loss rate, color, and texture characteristics of thick-shelled mussels (Mytilus coruscus). Additionally, changes in the microstructure were observed through hematoxylin-eosin (HE) staining and scanning electron microscopy (SEM), and protein properties and structure were determined. The results showed that as heating time increased, the drip loss rate, a* value, b* value, hardness, elasticity, cohesiveness and chewiness in all five treatment groups increased continuously, while the L* value first increased and then decreased. The results of HE staining and SEM showed that with the increase in heating time, the gap between muscle fibers in the five treatment groups increased, accompanied by varying degrees of muscle fiber fracture. The integrity of muscle fibers was maintained well after 3 min VH treatment. The results of gel electrophoresis showed that the proteins of M. coruscus underwent different degrees of thermal degradation and aggregation as heating time increased. The relative contents of β-fold and random coil in all five treatment groups first increased and then leveled off as heating time was extended. Meanwhile, the extraction rate of myofibrillar protein, Ca2+-ATPase activity, the relative contents of α-helix and β-turn decreased initially and then leveled off with increasing heating time. In the early stage of heating, the extraction rate of myofibrillar protein, Ca2+-ATPase activity, and the relative contents of α-helix and β-turn in the MH and AH groups were higher than those in the BH, SH, and VH groups. In summary, considering both the eating quality and practical conditions, SH and VH are the most suitable heat processing methods for M. coruscus, and the optimal heating time for improved mussel quality was 2 minutes. The findings of this study provide a reference for the development and quality control of shellfish products.